Socio-economic studies with social accounting and sociodemographic matrices : an (attempted) application to Mozambique - Santos, Susana (2016)
In looking for empirical evidence about the activity of countries, a proposal is made for studying (measuring and modelling) the activity of countries through the use of Social Accounting Matrices (SAMs) and Socio-Demographic Matrices (SDMs). SAMs and SDMs are presented as tools that have specific features for conducting studies in several different areas, as well as for supporting policy decision processes. Based on methodological principles that are derived mainly from the works of Richard Stone, emphasis is placed on the desirability of working in a matrix format, which includes not only people (SDM), but also, at the same time, activities, products, factors of production and institutions (SAM). This is considered to be a way of capturing the relevant network of linkages and the corresponding multiplier effects for the subsequent modelling of the act ivity of the countries studied. A method will be proposed for the construction of these matrices. In the case of the SAMs, it is proposed that their design and construction should adopt, at least as their starting point, the latest version of the System of National Accounts (2008 SNA) and the corresponding results of its adoption/adaptation by different countries. The exposition of this proposal is accompanied by an example applied to Mozambique, as well as by some considerations about the quality, suitability and completeness of the data used in the construction of SAMs and SDMs.